2013
DOI: 10.3109/00016489.2013.779022
|View full text |Cite
|
Sign up to set email alerts
|

Suturing silastic sheet from outside into larynx cavity: measurement of angles and clinical practice

Abstract: The mean value of the upper puncture angle was 30° (range 23.5-39°) while the lower puncture angle was also 30° (24-40°). Surgery procedures for implanting silastic sheets succeeded in 20 patients by extra-endolaryngeal puncture access. The average numbers of upper and lower punctures were 2 and 1.6, respectively. At follow-up none of the 20 patients had webs or had only 1 mm adhesion area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…5 One study found that 25% of larynges (5 of 20) could not be exposed with a large laryngoscope, thus precluding the use of the Lichtenberger endo-extralaryngeal suture passer in these patients. 3 Thus, there are circumstances in which an alternate technique must be employed for keel placement. The use of percutaneously placed devices for passing sutures from the external neck to within the larynx has been previously described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 One study found that 25% of larynges (5 of 20) could not be exposed with a large laryngoscope, thus precluding the use of the Lichtenberger endo-extralaryngeal suture passer in these patients. 3 Thus, there are circumstances in which an alternate technique must be employed for keel placement. The use of percutaneously placed devices for passing sutures from the external neck to within the larynx has been previously described.…”
Section: Discussionmentioning
confidence: 99%
“…The use of percutaneously placed devices for passing sutures from the external neck to within the larynx has been previously described. 2,3 Matrka and Simpson 2 depicted the use of angiocatheters and Zhang et al 3 described employing hollow-bore needles for this purpose. Although these methods avoid the need for the Lichtenberger needle passer, they can be technically challenging, as they require threading a suture through a small aperture using endoscopic instruments.…”
Section: Discussionmentioning
confidence: 99%
“…Occasional difficulties in microscopic laryngeal exposure and needle carrier unavailability are main abstacles. 2,4,5…”
Section: Discussionmentioning
confidence: 99%
“…Liyanage et al 4 described a lateral‐to‐lateral transfixation technique through the cricothyroid membrane but unfortunately with improper keel placement. Zhang et al 5 described inferior and superior punctures through the cricothyroid and thyrohyoid membranes, respectively. Through these needles, they struggled to manipulate the Prolene thread—first from outside‐inside through an inferior puncture, then from inside‐out through a superior puncture.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al . [7] published a study of 14 cadavers and twenty patients to determine reasonable extra-endolaryngeal puncturing sites and angles for implantation of laryngeal silastic sheet.…”
Section: Discussionmentioning
confidence: 99%